New Biofortification Tool: Wheat TaCNR5 Enhances Zinc and Manganese Tolerance and Increases Zinc and Manganese Accumulation in Rice Grains - Qiao, Kun; Wang, Fanhong; Liang, Shuang; Wang, Hong; Hu, Zhangli; Chai, Tuanyao (Journal of agricultural and food chemistry, 2019)
Heavy metal contaminants and nutrient deficiencies in soil negatively affect crop growth and human health. The plant cadmium resistance (PCR) protein transports heavy metals. The abundance of PCR is correlated with that of cell number regulator (CNR) protein, and the two proteins have similar conserved domains. Hence, CNR might also participate in heavy metal transport. We isolated and analyzed TaCNR5 from wheat (Triticum aestivum). The expression level of TaCNR5 in the shoots of wheat increased under cadmium (Cd), zinc (Zn), or manganese (Mn) treatments. Transgenic plants expressing TaCNR5 showed enhanced tolerance to Zn and Mn. Overexpression of TaCNR5 in Arabidopsis increased Cd, Zn, and Mn translocation from roots to shoots. The concentrations of Zn and Mn in rice grains were increased in transgenic plants expressing TaCNR5. These roles of TaCNR5 in the translocation and distribution of heavy metals mean that it has potential as a genetic biofortification tool to fortify cereal grains with micronutrients.